ANTISIPASI YURIDIS MENJERAT PELAKU TINDAK PIDANA MONEY LAUNDERING (PENCUCIAN UANG) - SRI RAHAYU PURWANI DJATI (Universitas Slamet Riyadi, 2009)
Abstract:Money laundrying is regarded as new species in Indonesian legal kaleidoscope. Not many know the ins and out of the operating mode in this crime while the effect of this to the government is not a little. The former IMF managing director, Michael Kamdessus estimated the money laundryng activities to absorb 600 billion USD annually which is equal to 2%-5% of GDP through out the globe. Therefore, how can Indonesian legal system anticipate the global scale of this crime. Keywords : Juridical Anticipation, Money Laundering